EVIDENCE-BASED MANAGEMENT OF ACUTE RHINOSINUSITIS WITH HERBAL PRODUCTS (International journal of artificial intelligence, 2025)
The overuse of antibiotics for unjustified indications such as the management of acute uncomplicated rhinosinusitis has contributed to the emergence of antibiotic-resistant strains of bacteria and prompted the need for alternative treatments. This review assesses the quality of evidence for the management of acute rhinosinusitis with herbal products, with the goal of positioning them among other treatments and identifying future research directions. Searches with Nacetylcysteine and mometasone furoate nasal spray (MFNS) were performed to compare the strength of evidence of herbal products to these conventional products, which are indicated for acute rhinosinusitis.